PENGARUH PRODUKSI BERAS, STOCK BERAS DAN INFRASTRUKTUR JALAN DAN JEMBATAN TERHADAP INFLASI DI SUMATERA SELATAN - Syamsurijal Syamsurijal (Jurnal Ekonomi Pembangunan, 2008)
The purpose of this research is to know the effects of rice production, rice stock, and road & brige condition on rate of inflation in South Sumatera province. The data used in this study are aggregative secondary data from year 2000 to year 2007, and are utilized to estimate a multiple regression modelÂ  in the form of double-logaritm. The results of estimation show that rice production, rice stock, and road & brige condition neither totally nor partially influence the rate of inflation in South Sumatera significantly. However, the results show that they are theoretically consistent with and support the expectation. It suggests that one who wants to do the same kind of further research, she or he should use disaggregative data to allow more variation in the data set in order to obtainÂ  sound results statistically. Key Words: Inflation, rice production, rice stock, and road & bridge condition.